2018
DOI: 10.11594/jtls.08.02.14
|View full text |Cite
|
Sign up to set email alerts
|

Home garden of local community in Pancasila Village for Biodiversity conservation and ecotourism sites development in Tambora Geopark, Sumbawa Island

Abstract: Home gardens in villages near conservation areas play an important role, both in ecological and socio-economical aspects. The aim of this research was to identify plant species diversity in home gardens in Pancasila Village, Tambora Geopark in the Sumbawa Islands. Floristic surveys were conducted at 25 home gardens in the local community. In-depth interviews with informants were conducted to generate information related to species value and home garden management. Results of the study show that 87plant species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Prior studies indicated that Musa spp. and Mangifera indica L. are commonly planted in home gardens throughout Indonesia, for example in Central Sulawesi [46], Lombok Island [54], Sumbawa Island [55], West Aceh [80], and Yogyakarta [81].…”
Section: Shg Plant Species' Major Use Categoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies indicated that Musa spp. and Mangifera indica L. are commonly planted in home gardens throughout Indonesia, for example in Central Sulawesi [46], Lombok Island [54], Sumbawa Island [55], West Aceh [80], and Yogyakarta [81].…”
Section: Shg Plant Species' Major Use Categoriesmentioning
confidence: 99%
“…Studies on HGs on several separate islands in Indonesia have been conducted, e.g., Sulawesi [46,47] Kalimantan [48][49][50], Bali [51,52], Sumatra [5,53], Lombok [54], Sumbawa [55], and Java Island [28,[56][57][58][59]. All these studies concerned individual HGs, which are very different from SHGs.…”
Section: Introductionmentioning
confidence: 99%
“…Some research on the homegarden in rural communes that are not affected by development projects, including dam project development in West Java and other rural areas, has been conducted (Swandayani et al 2016;Alelang et al 2018;Hakim and Hong 2018;Paembonan et al 2018;Prihatini et al 2018;Silalahi and Nisyawati 2018;Wakhidah et al 2020;Irham et al 2021). However, research on the homegarden system in rural communities affected by dam development is still rare.…”
Section: Introductionmentioning
confidence: 99%